Ibn Miskawiyah’s Theory of Evolution and Iqbal - Sulemani, Urwa Waheed; Zaidi, Syed Shiraz Ali (sourcecoder, 2024)
Ibn Miskawiyah presented theories on the history, psychology, ethics, evolution, metaphysics, mind, education. Iqbal gives special importance to Ibn Miskawiyah in his book “Reconstruction of Religious Thought in Islam”. Iqbal consider him among the Neo-Platonist Aristotelians of Iran. In the Reconstruction of Religious Thought in Islam, Iqbal also has admirable views for Ibn Miskawiyah. And he calls him a great Muslim philosopher. Paying particular attention to Ibn Miskawiyah’s metaphysics and theory of evolution, he says that Ibn Miskawiyah was the first Muslim thinker to present a clear and in many respects completely modern theory of the origin of man. Iqbal gave special importance to the theory of evolution of Ibn Miskawiyah. Iqbal likes the concept of movement of Ibn Miskawiyah and admires it. Because according to Iqbal, the evolutionary concept of the universe is the complete representation of Muslim thought and philosophy. Ibn Miskawiyah’s concept of evolution has a spiritual dimension. According to him, the cause of evolution is the dynamic of evolution within the objects. This evolution is related to the soul. In Iqbal’s theory of evolution, Iqbal seems convinced of the evolution of Khudi. And it is only through evolution of khudi that man can declare himself entitled to the caliphate of God on this earth. Ibn Miskawiyah’s theory of evolution became a means of bringing Muslim thought and philosophy to heights through which Muslim philosophy was able to establish its own high position apart from Greek influences. According to Iqbal, the main difference between the ideas of the Muslims and the Greeks is a dynamic concept of the universe, the philosophy of the Greeks is generally of a still and static universe, while on the contrary, the Muslim thinkers presented a clear and detailed concept of the evolution of life. And this evolution is actually Iqbal’s vision. The basis of Ibn Miskwiyah’s concept of God is upon the beliefs of Islam. Although in some places he follows Greek ideas. However, ultimately his theories are according to Islamic beliefs. And Iqbal is a complete follower of Islamic teachings in his concept of God and does not like to follow Greek ideas in any way.